1992
DOI: 10.1002/micr.1920130517
|View full text |Cite
|
Sign up to set email alerts
|

Endothelialization of microporous polytetrafluoroethylene grafts in the infrarenal aorta and caval vein of the rat

Abstract: To study healing and endothelialization of vascular grafts, microporous polytetrafluoroethylene (PTFE) prostheses 2 mm in inner diameter and 5 mm long were implanted into the infrarenal aorta or caval vein of the rat. Patency was assessed in six rats from each group at days 3, 7, 14, 28, and 56 after implantation. Four grafts were occluded, two in the aorta (56 days) and two in the caval vein (3 and 14 days). The prostheses were examined via scanning electron and light microscopy for evaluation of endotheliali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As a consequence, far too short grafts of 10-to 15-mm length were implanted. [19][20][21][22][23][24][25] If one conservatively extrapolates the transanastomotic outgrowth rates in rats, 22,25,26 it is highly likely that these experimental grafts were all transanastomotically fully endothelialized within less than 10 weeks. Given the individual variability of transanastomotic outgrowth, transanastomotic confluence needs to be assumed even earlier.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, far too short grafts of 10-to 15-mm length were implanted. [19][20][21][22][23][24][25] If one conservatively extrapolates the transanastomotic outgrowth rates in rats, 22,25,26 it is highly likely that these experimental grafts were all transanastomotically fully endothelialized within less than 10 weeks. Given the individual variability of transanastomotic outgrowth, transanastomotic confluence needs to be assumed even earlier.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the endothelialization of PTFE grafts of 5 mm length was more rapid in the caval vein than in the aorta of the rat, prob- ably due to a more efficient formation of mural thrombus (26). At the venous side, slow blood flow and low blood pressure may obviously facilitate formation of mural thrombus, which in turn may enhance endothelialization.…”
Section: Discussionmentioning
confidence: 99%
“…Zdanowski et al5 reported endothelialization after placement of a PTFE graft (2 mm inner diameter; 5 mm long) in the caval vein of rats. Fourteen days after implantation, endothelialization of the inner surface of the graft was found to have been completed.…”
Section: Discussionmentioning
confidence: 99%